1977
DOI: 10.1002/aja.1001490205
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of tooth development in vitro following sodium fluoride treatment

Abstract: Mandibular incisors were dissected from the jaw of 15- and 16-day C57BL/10 mouse embryos and cultured on agar-solidified Eagle's basal medium supplemented with fetal calf serum, an antibiotic, and glutamine, The experimental medium was the same as the control except that fluoride was added such that the final concentrations ranged from 2.0-8.0 mM NaF. Control and experimental explants were recovered after two, four and six days of incubation and studied histologically. After two days of fluoride treatment (3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Almost no effects of fluoride on odontogenic cell differentiation were detected at F50 ÌM peak plasma fluoride concentrations [Walton and Eisenmann, 1974] and up to 265 ÌM in culture medium [Bronckers et al, 1984a], although at higher concentrations (3 mM) a delay in differentiation was reported [Kerley and Kollar, 1977].…”
Section: Cell Differentiation and Functional Morphologymentioning
confidence: 99%
“…Almost no effects of fluoride on odontogenic cell differentiation were detected at F50 ÌM peak plasma fluoride concentrations [Walton and Eisenmann, 1974] and up to 265 ÌM in culture medium [Bronckers et al, 1984a], although at higher concentrations (3 mM) a delay in differentiation was reported [Kerley and Kollar, 1977].…”
Section: Cell Differentiation and Functional Morphologymentioning
confidence: 99%
“…There is no evidence that exposure of developing teeth to physiological levels of fluoride, in vivo (Smith et al, 1993) and in organ culture (Kerley and Kollar, 1977;Levenson, 1980;Bronckers et al, 1984a;Bawden et al, 1992), affects tooth morphogenesis, cell proliferation, or differentiation of ameloblasts. Even in highly fluorotic teeth, the size and form of the teeth are not changed (e.g., Kierdorf and Kierdorf, 1997).…”
Section: Effects Of Fluoride On Amelogenesis Proliferating and Differmentioning
confidence: 99%
“…Even in highly fluorotic teeth, the size and form of the teeth are not changed (e.g., Kierdorf and Kierdorf, 1997). In organ culture, proliferating and differentiating pre-ameloblasts are very resistant to fluoride, and fluoride's effects on cell morphology and matrix synthesis have been reported only in the range of 1.3-5.2 mmol F/L (Kerley and Kollar, 1977;Levenson, 1980;Bronckers et al, 1984a;Bronckers and Wöltgens, 1985;Li et al, 2005), which is far higher than the plasma levels that can induce enamel fluorosis in vivo.…”
Section: Effects Of Fluoride On Amelogenesis Proliferating and Differmentioning
confidence: 99%
“…Previous investigators have suggested that fluoride affects ameloblast proliferation and differentiation [Kerley and Kollar, 1977;Holland and Hongslo, 1979], ameloblast morphology [Smith et al, 1993], matrix composition and degradation [DenBesten and Crenshaw, 1984;DenBesten and Hefferman, 1990] and matrix-mineral binding [Aoba et al, 1989]. However, many of these results have been equivocal or only present at very high levels of fluoride exposure (notably in the culture fluid for in vitro work) which are not typical of those generally associated with dental fluorosis.…”
Section: Discussionmentioning
confidence: 62%